Daniel Webster and Jacksonian Democracy - Nathans, Sydney (Johns Hopkins University Press, 2019)
Originally published in 1973. Professor Nathans illuminates the changes wrought by Jacksonian democracy on the career of Daniel Webster, a major political figure, and on the destiny of a major political party, the Whigs. Daniel Webster was a creative anachronism in the Jacksonian era. His career illustrates the fate of a generation of American politicians, reared to rule in a traditional world of defined social classes where gentlemen led and the masses followed. With extensive research into primary sources, Nathans interprets Webster as a leader in the older political tradition, hostile to permanent organized political parties and fearful of social strife that party conflict seemed to promote. He focuses on Webster's response to the rise of entrenchment of voter-oriented partisan politics. He analyzes Webster's struggle to survive, comprehend, and finally manipulate the new politics during his early opposition to Jackson; his roles in the Bank War and the nullification crisis; and the contest for leadership within the Whig Party from 1828 to 1844. Webster and the Whigs resisted and then belatedly attempted to answer the demands of the new egalitarian mass politics. When Webster failed as an apologist for government by the elite, he became a rhapsodist of American commercial enterprise. Seeking a new power base, he adapted his public style to the standards of simplicity and humility that the voters seemed to reward. Nathans shows, however, that Webster developed a realistic vision of the common bonds of Jacksonian society-of the basis for community-that would warrant anew the trust needed for the kind of leadership he offered. The meaning of Webster's career lies in these attempts to bridge the old and new politics, but his attempt was doomed to ironic and revealing failure. Nathans studies Webster's impact on the Whig party, showing that his influence was strong enough to thwart the ambitions of his rivals Henry Clay and John C. Calhoun but not strong enough to achieve his own aspirations. Nathans argues that Webster, through his efforts to increase his authority within the party, merely revealed his true weakness as a sectional leader. His successful blocking of Clay and Calhoun brought about a deadlock that significantly hastened the transfer of power to men more committed to strong party organization and more talented at voter manipulation. Webster's dilemma was the crisis of an entire political generation reared for a traditional world and forced to function in a modern one.